2021
DOI: 10.1136/annrheumdis-2021-eular.553
|View full text |Cite
|
Sign up to set email alerts
|

Op0129 belimumab After Rituximab Significantly Reduced Igg Anti-Dsdna Antibody Levels and Prolonged Time to Severe Flare in Patients With Systemic Lupus Erythematosus

Abstract: Background:B cell depletion with rituximab, an anti-CD20 mAb, has shown efficacy for systemic lupus erythematosus (SLE) in open-label studies but failed to meet primary endpoints in two randomised, placebo controlled trials. Rituximab increases BAFF levels which has been associated with subsequent lupus flares. We hypothesised that high BAFF levels after rituximab limit its effectiveness in SLE and that the anti-BAFF monoclonal antibody belimumab given immediately after rituximab could be a valuable therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The overall safety of belimumab, rituximab, and belimumab + rituximab sequential treatment in this study was consistent with the known individual safety profiles for belimumab and rituximab (21,34,58). Although the safety profile of belimumab + rituximab in pSS has not been explored widely, this combination has previously demonstrated acceptable safety profiles in case studies of patients with pSS (50,57), as well as in previously published phase II studies of patients with SLE or LN, which are consistent with the results shown in this study (59)(60)(61). Overall, there were no imbalances of clinical concern in the incidence of reported AEs or AEs of special interest (AESIs; malignant neoplasms, PASR, infections, depression, suicide/self-injury) across treatment groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The overall safety of belimumab, rituximab, and belimumab + rituximab sequential treatment in this study was consistent with the known individual safety profiles for belimumab and rituximab (21,34,58). Although the safety profile of belimumab + rituximab in pSS has not been explored widely, this combination has previously demonstrated acceptable safety profiles in case studies of patients with pSS (50,57), as well as in previously published phase II studies of patients with SLE or LN, which are consistent with the results shown in this study (59)(60)(61). Overall, there were no imbalances of clinical concern in the incidence of reported AEs or AEs of special interest (AESIs; malignant neoplasms, PASR, infections, depression, suicide/self-injury) across treatment groups.…”
Section: Discussionsupporting
confidence: 90%
“…The hypothesis that sequential belimumab + rituximab treatment may result in an improved clinical response has been supported by controlled, randomized clinical trials in patients with SLE and several small case studies ( 50 , 55 – 57 , 60 , 72 ). One case study in particular reported long-term efficacy and safety of belimumab + rituximab in pSS ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SLE, pilot trials and observational studies were initially promising but larger scale clinical trials did not show a clear benefit. Recent trials of a combination of Belimumab, which targets the cytokine BLyS with Rituximab, however, show promise in SLE (216). Direct cross-linking of CD20 on B cell tumour cell lines was shown to be sufficient for the induction of apoptosis through MAP kinase activation (212, (190,191,193,199,201,207) A brief summary of the clinical features and immune compartment involvement in adult and paediatric liver diseases.…”
Section: Targeting B Cells In the Liver -Rituximab Treatmentmentioning
confidence: 99%